2016
DOI: 10.1021/jacs.6b03710
|View full text |Cite
|
Sign up to set email alerts
|

Surface cis Effect: Influence of an Axial Ligand on Molecular Self-Assembly

Abstract: Adding ligands to molecules can have drastic and unforeseen consequences in the final products of a reaction. Recently a surface trans effect due to the weakening of a molecule-surface bond was reported. Here, we show a surface cis effect where an axial ligand at adsorbed transition-metal complexes enables lateral bonding among the molecules. In the absence of this ligand, the intermolecular interaction is repulsive and supramolecular patterns are not observed. Fe-tetramethyl-tetraazaannulene on Au(111) was in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 67 publications
0
6
0
Order By: Relevance
“…A related switching of intermolecular interactions by attaching a ligand to a molecule has recently been reported for Fe-tetramethyl-tetraazaannulene on Au(111). 47…”
Section: B Intermolecular Interactionsmentioning
confidence: 99%
“…A related switching of intermolecular interactions by attaching a ligand to a molecule has recently been reported for Fe-tetramethyl-tetraazaannulene on Au(111). 47…”
Section: B Intermolecular Interactionsmentioning
confidence: 99%
“…Simultaneously, porphyrinoid derivatives have drawn the interest of the surface science community, , which, equipped with state of the art scanning probe microscopies and complemented by photoemission spectroscopies and DFT calculations, has studied corroles, , porphycenes, porphyrins, subphthalocyanines, , phthalocyanines, and naphthalocyanines . This topic of research is currently quite broad including self-assembly, , on-surface synthesis, , electronic structure, , in situ metalation, information storage and electronic switching, ,,, nanomagnetism, , electroluminescence, ,, ligation of axial adducts, ,, and catalysis. However, despite the envisioned potential of expanded porphyrinoids, all reported studies on surfaces have been limited to tetrapyrrolic-like or smaller macrocycles.…”
Section: Introductionmentioning
confidence: 99%
“…Organic spintronics is a fertile research field aiming at using organic materials for spin transport. Recently, the control of the magnetization of a molecule by the substrate and the control of the substrate magnetization by adsorbed molecules have been reported. Moreover, the magnetization of molecules can be tuned, for example, through their ligands or by using functional molecules such as spin-crossover molecules which intrinsically possess different magnetic states. Yet, while most of the organic-spintronic studies considered molecules comprising a metal center, metal-free molecules adsorbed on surfaces can nevertheless develop large spin-polarization or carry a magnetic moment because of unpaired electrons. Furthermore, Karan et al , recently reported that the magnetic moment within metal-free organic molecules adsorbed on Au(111) can be reversibly switched on and off.…”
Section: Introductionmentioning
confidence: 99%